Sinonasal Mucosal Melanoma: An Update and Review of the Literature. (22nd June 2022) - Salari, Behzad; Foreman, Ruth K.; Emerick, Kevin S.; Lawrence, Donald P.; Duncan, Lyn M.
Abstract: Primary sinonasal mucosal melanoma (SNMM) is an aggressive tumor with high metastatic potential and poor outcomes. Presenting symptoms are nonspecific, and the nasal cavity is the most common site of origin followed by the maxillary and ethmoid sinuses. Histopathologically, SNMMs are pleomorphic and predominantly composed of epithelioid cell type. Identifying these tumors requires a high index of suspicion for melanoma and the use of a panel of immunohistochemical markers when typical histopathological features are missing. Not infrequently, these tumors are undifferentiated and/or amelanotic. Currently, SNMM falls into 2 different staging systems proposed by the American Joint Committee on Cancer, one for carcinoma of the nasal cavity and sinuses and the other for head and neck melanoma. Although therapeutic standards do not exist, surgical resection with adjuvant radiotherapy and/or systemic therapy may offer the best outcome. Lymphadenectomy including possible parotidectomy and neck dissection should be considered in patients with regional lymph node metastasis. However, the role of elective lymph node dissection is controversial. Genetic profiling has identified a number of recurrent gene mutations that may prove useful in providing targets for novel, emerging biological treatments. In this article, we provide an update on clinicopathological features, staging, molecular discoveries, and treatment options for SNMM.